Analysis of Cleaning Service Work Postures to Reduce Musculoskeletal Injuries with the Posture Evaluation Index Approach - Debora, Sevialita; Suryadi, Akmal (Journal La Multiapp, 2025)
Ergonomics is one of the important concepts to be applied in the work environment in achieving occupational safety and health. Work postures during work that arise due to the active movement of several limbs with postures that are not ergonomic can pose a risk to workers. Musculoskeletal injuries generally occur due to excessive muscle contractions due to poor work attitudes and the provision of workloads that are too heavy with a long duration of loading. With the aim of this study is to determine the correct work posture using the Posture Evaluation Index so as to prevent and reduce Musculoskeletal injuries in Cleaning Service Employees at Hang Tuah 5 Sidoarjo High School. With the method used is PEI, which is a score parameter in the assessment of work postures included in the OWAS method and integrated with other studies such as RULA and REBA. In this study with a total of 10 employees in lifting gallons / goods, it can be seen that the unergonomic work posture resulted in a PEI value of 2.791 including the high category and improvements must be made immediately in the workplace area.